Some N-(5-methyl-1,3,4-thiadiazol-2-yl)-4-[(3-substituted)ureido/ thioureido]benzenesulfonamides as carbonic anhydrase I and II Inhibitors - TÜRK, Sevda; TOK, Fatih; ÇELİK, Hülya; KARAKUŞ, Sevgi; NADAROĞLU, Hayrunnisa; KOÇYİĞİT-KAYMAKÇIOĞLU, Bedia; KÜÇÜKOĞLU, Kaan (My University, 2017)
In the present study, N-(5-methyl-1,3,4-thiadiazol-2-yl)- 4-[(3-substituted)ureido]benzenesulfonamide (1-9) and N-(5-methyl-1,3,4-thiadiazol-2-yl)-4-[(3-substituted) thioureido]benzenesulfonamide (10-14) derivatives were synthesized from 4-amino-N-(5-methyl-1,3,4-thiadiazol-2-yl) benzenesulfonamide (sulfamethizole). All new compounds were characterized by elemental analysis and various spectroscopic methods (FTIR, 1 H-NMR and MS). These new sulfonamide derivatives were investigated as inhibitors of carbonic anhydrase especially human carbonic anhydrase I and II. The new compounds showed higher activity against the human cytosolic CA I (IC50 values 0.144-15.65 nM) and CA II (IC50 values 0.109- 17.95 nM) in comparison with the clinically used CA inhibitor acetazolamide
Keywords: Carbonic anhydrase inhibitors, sulfonamide, sulfamethizole, urea and thiourea